Răspunsuri

2014-02-06T13:37:17+02:00
M- meri
p- pruni
c- ciresi
t- totalul pomilor
c= 93-(m+p)
c= 93-58
c=35 => p=69-c=69-35=34

m=93-(p+c)
m=93-69
m=24
2014-02-06T13:37:30+02:00
Pai scri ca:meri+pruni+ciresi=93
                meri+pruni=58 rezulta ca meri=58-pruni
                pruni+ciresi=69 rezulta ca ciresi=69-pruni
Acum inlocuim in suma: 58-pruni+pruni+69-pruni=93
                                    58+69-pruni=93
                                       127-pruni=93 rezulta ca pruni=127-93 adica pruni=     34
acum rezulta ca meri=58-34=   24
                         ciresi= 69-34=   35